SEMA: utilizing multi-sensory cues to enhance the art experience of visually impaired students - Welewatta, Ruwani; Maithripala, Akila; Weerasinghe, Heshan; Karunanayake, Kasun; Sandaruwan, Damitha; Arachchi, Samantha Mathara; Cheok, Adrian David (Frontiers in Computer Science, 2024)
Assistive technologies play a major role in bridging the accessibility gap in arts (especially paintings). Despite the constant advancements in these areas, the visually impaired often encounter challenges in independently experiencing and interpreting paintings. Our goal was to effectively convey the contents of a painting to visually impaired students using selected multi-sensory stimuli (tactile, auditory, and somatosensory) to compensate for the loss of input from the sense of sight. A prototype (named SEMA—Specially Enhanced Multi-sensory Art) was developed around a simple painting to incorporate descriptive outputs of the aforementioned stimuli. The prototype was developed and refined iteratively with the visually impaired students at the University of Colombo, Sri Lanka. We evaluated all the systems individually using the user feedback and several quantitative and qualitative measures were adopted to analyze the results. The final user study with 22 visually impaired participants yielded a strong preference (92.6 %) for the prototype and highlighted its potential to enhance the art experiences. The findings of this study contribute to the further exploration of multi-sensory integration in entertainment and its impact on the visually impaired community.